PEMANFAATAN JENIS-JENIS MANGROVE SEBAGAI PRODUK MAKANAN OLAHAN DI MUARA BADAK ULU, KUTAI KARTANEGARA - Rita Diana; Paulus Matius; Hastaniah Hastaniah; Sutedjo Sutedjo; Cicha Rantika Meilani; Esti Handayani Hardi; Haris Retno Susmiyati; Nurul Puspita Palupi (ABDIKU: Jurnal Pengabdian Masyarakat Universitas Mulawarman, 2022)
Food production derived from processed types of mangroves fruit does not appear to have been widely developed or in demand by the Muara Badak community. Many people are unaware that mangrove fruit can be consumed and used as food or snacks. The potential and benefits of mangroves as a food source are still unknown and underutilized. This activity aims to disseminate information about the benefits of various types of fruit processing mangroves into processed food products through socialization. Sonneratia ovata (Pedada), a variety of mangroves that grows abundantly on the river's edge in the village of Muara Badak Ulu, is one of them. This activity was carried out on farmers and communities in the Salo Sumbala watershed in Kutai Kartanegara Regency, Muara Badak Subdistrict, and Muara Badak Ulu village. The approach taken in this activity is to lecture and provide knowledge about the many species of mangroves found in the vicinity of Muara Badak Ulu, particularly the Salo Sumbala watershed, which has the potential to produce processed food from mangrove fruit.